A Feasibility Study of Expanded Home-Based Telerehabilitation After Stroke - Cramer, Steven C.; Dodakian, Lucy; Le, Vu; McKenzie, Alison; See, Jill; Augsburger, Renee; Zhou, Robert J.; Raefsky, Sophia M.; Nguyen, Thalia; Vanderschelden, Benjamin; Wong, Gene; Bandak, Daniel; et al. (Frontiers in Neurology, 2021)
Introduction: High doses of activity-based rehabilitation therapy improve outcomes after stroke, but many patients do not receive this for various reasons such as poor access, transportation difficulties, and low compliance. Home-based telerehabilitation (TR) can address these issues. The current study evaluated the feasibility of an expanded TR program. Methods: Under the supervision of a licensed therapist, adults with stroke and limb weakness received home-based TR (1 hour/day, 6 days/week) delivered using games and exercises. New features examined include extending therapy to 12 weeks duration, treating both arm and leg motor deficits, patient assessments performed with no therapist supervision, adding sensors to real objects, ingesting a daily experimental (placebo) pill, and generating automated actionable reports. Results: Enrollees (n=13) were median age 61 [IQR 52-65.5], and 129 [52-486] days post-stroke. Patients initiated therapy on 79.9% of assigned days and completed therapy on 65.7% of days; median therapy dose was 50.4 [33.3 - 56.7] hours. Non-compliance doubled during weeks 7-12. Modified Rankin scores improved in 6/13 patients, 3 of whom were > 3 months post-stroke. Fugl-Meyer motor scores increased by 6 [2.5-12.5] points in the arm and 1 [-0.5 - 5] point in the leg. Assessments spanning numerous dimensions of stroke outcomes were successfully implemented; some, including a weekly measure that documented a decline in fatigue (p=0.004), were successfully scored without therapist supervision. Using data from an attached sensor, real objects could be used to drive game play. The experimental pill was taken on 90.9% of therapy days. Automatic actionable reports reliably notified study personnel when critical values were reached. Conclusions: Several new features performed well, and useful insights were obtained for those that did not. A home-based telehealth system supports a holistic approach to rehabilitation care, including intensive rehabilitation therapy, secondary stroke prevention, screening for complications of stroke, and daily ingestion of a pill. This feasibility study informs future efforts to expand stroke TR. Clinicaltrials.gov ID # NCT03460587